Perencanaan Strategis Pengelolaan Limbah Medis Fasyankes Dan Evaluasi Risiko Kontaminasi Lingkungan Di Era Digital - Helen Desi Maria Pasaribu; Nur Chofifa Mamonto; Sabina Rusdi; Chanaya Queen Tampung; Naysilla Timomor; Meiton Tabuni; Fauzi Nurhamidin; Agustinus Robin Butarbutar (STIKES Columbia Asia Medan, 2026)
Medical waste is a by-product of healthcare activities that may have negative impacts on human health and the environment if not properly managed. This study aims to examine strategic planning for medical waste management in healthcare facilities and evaluate the risk of environmental contamination in the digital era. The method used was a literature review by examining various relevant scientific sources. The findings indicate that medical waste management still faces several challenges, including non-compliance with established standards, limited human resources, and the risk of environmental pollution. The utilization of digital technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), RFID, and Blockchain has the potential to improve the effectiveness of monitoring and managing medical waste. Therefore, strategic planning supported by digital technology, human resource capacity building, and regulatory compliance is essential for achieving safe and sustainable medical waste management.